Front Matter (Journal of the Assembly for Expanded Perspectives on Learning, 2007)
Editors' Message Whitman writes in "Reconciliation": For my enemy is dead, a man divine as myself is dead, I look where he lies, white-faced and still, in the coffin—I draw near, Bend down and touch lightly with my lips the white face in the coffin. In that act, in a gentle kiss that joins self and enemy, he reconciles and eases the pain of war's devastation. For Whitman, reconciliation is the "Word over all, beautiful as the sky," the deed that washes the world clean of the carnage of conflict. Without the act of reconciliation—the bringing together of that which was divided, of that which was estranged—the "soil" of war, its blood feuds, its hate, its fears, and its enmities—would linger to pollute the promise of a country and its people. Reconciliation is necessary to heal, to move on, to be at peace with, and to again flourish as a people in a nation once violently divided against itself and estranged. Teaching, too, relies on an ongoing act of reconciliation. Good teaching, Parker Palmer reminds us, comes from identity and integrity, and both have "as much to do with our shadows and our limits, our wounds and fears, as with our strengths and potentials" (13). To teach requires reconciling shadows and limits, wounds and fears with strengths and potentials: our own and our students'. The seven essays in this issue of JAEPL "bend down and touch lightly" fears, woes, and strengths to bring about a fruitful union of pain and healing; they do the work of reconciliation so necessary in teaching and in writing, pointing to ways in which we might similarly reconcile our own tensions. We open with a poignant plea from bell hooks for the work of reconciliation, a necessary prelude, she says, for writing and healing. Without reconciliation, she points out, writing cannot be therapeutic, it cannot heal that which is broken. The six essays that follow her supplication offer specific moments and specific methods of reconciliation, seeking to bring again into harmony relationships and forces that tug against each other. Devan Cook focuses on one of the most contentious and painfully fraught sites in composition studies: the first-year Writing Program and the difficult negotiation among students, administration, and adjunct faculty. Beyond reconciling the "breakdowns in communication between students and their instructor" that disrupt teaching and learning, a writing program administrator (WPA) must confront and attempt to reconcile the whirlpool of tensions swirling around "emotional labor." Cook argues that "teaching involves emotional labor as well as knowledge and creative work," and, while asking adjunct and contingent faculty to engage in this emotional labor is necessary, it is "at the same time highly problematic, given the conditions of their work." Thus, reconciliation functions for Cook in her role as a WPA on multiple complex levels: practical, interpersonal, discursive, and institutional. While addressing these tensions is difficult emotional labor for any WPA, it is essential for the well being of teachers, students, and institutions. Moving from the emotional and intellectual tensions within writing program administration, we turn to two essays that examine from different perspectives the constant movement of reconciliation necessary to honor the goals of a Jesuit-inspired pedagogical philosophy: cura personalis, or care for the whole student. In "Dangerous Pedagogy," Elizabeth B. Gardner. Patricia E. Calderwood, and Roben Torosyan jointly engage in an exploration of two techniques Gardner uses in her undergraduate psychology classes to bring together students' personal and intellectual lives: brief "What's on Your Mind" discussions and Insight Cards. While student evaluations reveal that such techniques foster a sense of community that enriches and deepens learning, the authors also conclude these methods are potentially dangers because they rely on constant reconciliation. They observe that "traditional student-teacher power relations became unmoored," and, while there was "room for the social, emotional, and spiritual dimensions of teacher and student to shape the process and the content of learning," those complex dimensions posed a threat. Teacher and students had to work collaboratively and continually to harmonize these tensions. Karen Surman Paley in "Applying 'Men and Women for Others' to Writing about Archeology" also tackles the complex pedagogical philosophy of cura personalis, secularized as "men and women for others," this time within the context of an archeology class unearthing the remains of a state orphanage. Through fine-grained case studies focusing on students' writing, Paley highlights the degree to which students developed through reconciliation. They enact reconciliation physically in moments when former residents of the long defunct orphanage returned to reunite and witness the class's work. Students also enact reconciliation intellectually as they struggle to determine what private information to include in their archeology reports from their interviews with former residents. And students reconcile emotionally as they experience the necessary union of intellectual inquiry with the humanity of the subject of inquiry. If reconciliation lends depth, and danger, to pedagogy, it also invites communal membership and engagement with literature. In "Reading Othello in Kentucky," a painful and humorous essay, Elizabeth Oakes and students in her graduate seminar on Shakespeare explore these two spheres of reconciliation. Inspired by Azar Nafisi's Reading Lolita in Tehran, an account of an unauthorized and highly illegal class Nafisi informally conducted with seven other women in Tehran, Oakes and her students explore the experience of Othering. They take their cue from Shakespeare's marginalization and manipulation of Othello, applying those lessons to their marginalization as Kentuckians. In the process they identify the tensions implicit within the literature, their response to the literature, and their own communal identity. Rachel Forrester brings us back to the individual act of reconciliation, particularly the resolution—or balancing—of tensions in writing. In "The 'Not Trying' of Writing" Forrester struggles with "the uncertainty and perhaps even deep dread" she experiences every time she begins to write. Writing is an act of faith, she says, faith in the power of "not trying" because, after all the hard work, all the preparation, the act itself is like hearing what to say rather than deciding what to say. Writing seems to "emerge in physical, black-and-white form." Her essay attests to the paradoxical necessity of not trying, tracking and harmonizing the tensions of writing through silence, the unconscious, and bodies. She finds in that reconciliation ways to bring into the classroom the "not trying" of writing. Finally, we conclude this exploration of reconciliation with an essay that seeks to reconcile through both its form and its content the tension between rules and freedom intrinsic to teaching. By playing with traditional academic discourse—performing it, disrupting it, transforming it—Eudora Watson, Jennifer Mitchell, and Victoria Levitt come to grips in different ways with the chafing necessity of seemingly arbitrary rules. In "The Other End of the Kaleidoscope: Configuring Circles of Teaching and Learning," the three authors enact reconciliation both emotionally and discursively, bringing into a tentative if only temporary harmony the difficult and troubling tension between the seemingly informal and formal rules of academe with the richness and necessary disorder of learning itself. If reconciliation is, as Whitman says, the "word over all," then these seven essays demonstrate through myriad perspectives that reconciliation is also a constant process, a matter of continual balance; it is more than a single act, completed when we have lightly touched the face of an enemy to discover our own divinity. Rather, these essays suggest that teaching, learning, writing, and reading may, in fact, derive their life's blood from our ongoing efforts to recognize and heal wounds through reconciliation. We bend down and lightly touch the tensions, the shadows, the limits of our classrooms and ourselves not once but always. Here is the necessary torque that powers the lives of teachers and learners. Works Cited Palmer, Parker J. The Courage to Teach: Exploring the Inner Landscape of a Teacher's Life. San Francisco: Jossey-Bass, 1998. Whitman, Walt. "Reconciliation." Leaves of Grass: Authoritative Texts, Prefaces, Whitman on His Art, Criticism. ED. Sculley Bradley and Harold W. Blodgett. New York: W. W. Norton. 1973. 320.